Controlador digital multi-amostras PID e V2 COT híbrido para regulador buck síncrono - Vasconselos, Renan Borges de (2018)
This work presents a hybrid digital control method for a point-of-load synchronous buck converter implemented in a digital signal processor, seeking to achieve high efficiency in light loads and good transitory responses. To present the control system proposal, a study of the modulation on buck converter is presented analyzing the impact on losses. The control methods are also presented, analyzing behavior and particularities of digital implementation with design methodology. In the proposal two different controllers are used, seeking out to join good characteristics while eliminating drawbacks under different load conditions. For light loads, a constant on-time pulse frequency modulation controller is used, in order to reduce power losses. For high loads, a linear pulse width modulation PID controller is applied due to its better stability, with improved transitory response achieved by multisampling. The study was carried out for a step-down power converter from 3.3V to 1.2V with a maximum load current of 5A. The feasibility of the proposed control method is shown with simulation and experimental results. An efficiency close to 90% was obtained for high loads with a reduction to 80% on the minimum load, the transient time results for load step remained between 100us and 150us.